Pembuatan Komposit Serat Tandan Kosong Sawit (TKS) Bermatriks Epoxy Dengan Metode Vacuum Bagging - Langgeng Budi Wibowo; Warman Fatra; Kaspul Anuar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Oil Palm Empty Fruit Bunches (OPEFB) are natural fibers that have potential as fillers or reinforcement for polymer composites in terms of physical properties, morphology, and chemical composition. The problem in previous research is the weak bond between the fiber and the matrix, which causes low mechanical properties. Composite manufacture in this study using OPEFB fiber and epoxy matrix with vacuum bagging method. OPEFB fiber with a length of 3 cm was extracted using 5% OPEFB ash with boiling temperatures of 40°C, 55°C, and 70°C, with a boiling time of 1, 2, 3 hours, and in the composite manufacturing process, silane coupling agent was added to the matrix with variation of fractions 1.5%, 2% and 2.5% of the matrix volume. Experimental design and variables affect tensile strength, impact strength and water absorption, to determine the experimental design and variables in this study using the Response Surface Methodology (RSM) statistical method. The results showed the maximum tensile strength at running 19 with a value of 21,859 MPa, with a temperature of 70°C, boiling time of 3 hours, and the addition of a matrix of 2.5%. The maximum impact strength at running 2 with a value of 215.96 J/m, with a temperature percentage of 70°C, boiling time of 3 hours, and the addition of a matrix of 1.5%. Minimum water absorption on running 19 with a value of 1.4%, with a temperature of 70°C, boiling time of 3 hours, and the addition of a matrix of 2.5%. Keywords: Oil Palm Empty Fruit Bunches, method Response Surface Methodology (RSM), Vacuum Bagging, silane coupling agent.